2015
DOI: 10.1039/c4ta06539e
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesized carbon nanotube superstructures with superior CO2and hydrogen storage capacity

Abstract: Carbon nanotube (CNT) superstructures prepared at 180 °C are activated to highly porous (1479–3802 m2g−1; 0.83–2.98 cm3g−1) carbons with excellent CO2uptake; up to 4.8 and 8.4 mmol g−1at 1 bar and 25 or 0 °C, respectively, and exceptional hydrogen storage; up to 7.5 and 14.9 wt% at −196 °C and 20 or 150 bar, respectively, and 4.4 wt% at 25 °C and 150 bar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
78
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 150 publications
7
78
2
Order By: Relevance
“…Py800 also shows an extremely high surface area of 4334 m 2 g −1 which, to our knowledge, is the highest reported to date for an organic derived activated carbonaceous material. [12,13,32] The nitrogen isotherms and pore size distributions for the synthesized carbons are shown in Figure S3 temperature was raised to 850 °C, the isotherms display some Type IVa character with a hysteresis loop gradually appearing at P/P 0 = 0.5, this is accompanied by a widening of the pore size distribution ( Figure S3b, Supporting Information) and is due to the formation of mesopores at higher activation temperatures. The higher temperatures led to a decrease in surface area from 3105 m 2 g −1 for Ben750 to 3049 and 2730 m 2 g −1…”
Section: Doi: 101002/adma201603051mentioning
confidence: 99%
See 3 more Smart Citations
“…Py800 also shows an extremely high surface area of 4334 m 2 g −1 which, to our knowledge, is the highest reported to date for an organic derived activated carbonaceous material. [12,13,32] The nitrogen isotherms and pore size distributions for the synthesized carbons are shown in Figure S3 temperature was raised to 850 °C, the isotherms display some Type IVa character with a hysteresis loop gradually appearing at P/P 0 = 0.5, this is accompanied by a widening of the pore size distribution ( Figure S3b, Supporting Information) and is due to the formation of mesopores at higher activation temperatures. The higher temperatures led to a decrease in surface area from 3105 m 2 g −1 for Ben750 to 3049 and 2730 m 2 g −1…”
Section: Doi: 101002/adma201603051mentioning
confidence: 99%
“…Ben750, Th850, and Py800 also show high H 2 uptakes of 4.0, 3.7, and 5.6 wt%, respectively at 10 bar/77.3 K, and all materials reach saturation under these conditions (Figure 3c). These are among the highest H 2 uptakes reported to date for any porous carbon materials at 10 bar, [13,45] and these relatively inexpensive materials outperform zeolite-, [46] carbide-, [47] and MOF-derived carbons. [48] Ben750 and Py800 also outperform the previously reported carbonized N-rich HCP, synthesized from a noncommercial monomer, which adsorbed 2.6 wt% H 2 at 1 bar and 77.3 K. [49] In summary, we have shown that carbonization of HCPs with KOH activation can be used to generate highly porous carbons that show attractive properties for CO 2 and H 2 adsorption.…”
Section: Doi: 101002/adma201603051mentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] This has included preparation of ultra-high surface area nanostructures for gas uptake at high pressures, 21,22 and on the other hand, synthesis of highly microporous materials for CO2 uptake at low pressure. 7,[33][34][35][36][37][38][39] Unfortunately, at the present time, the materials with the highest surface area generally tend to have low packing density and therefore low volumetric uptake. Enhancements in packing density and consequently volumetric storage capacity of porous materials may be achieved by material densification or compaction.…”
mentioning
confidence: 99%